2016
DOI: 10.1016/j.juro.2015.03.094
|View full text |Cite
|
Sign up to set email alerts
|

Vesicoureteral Reflux Index: 2-Institution Analysis and Validation

Abstract: The vesicoureteral reflux index is a simple tool that reliably predicts significant improvement and spontaneous resolution of primary reflux in patients diagnosed at younger than 2 years. The index provides valuable prognostic information, facilitating individualized patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 34 publications
2
25
0
1
Order By: Relevance
“…Patients with a lower VURx have a greater probability of spontaneous resolution. Therefore, the VURx reliably predicts primary VUR improvement/resolution in children . The distal UDR is calculated as the widest diameter of the distal ureter in the false pelvis divided by the distance between L1 and L3 …”
Section: Are There Any Alternatives To Vcug?mentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with a lower VURx have a greater probability of spontaneous resolution. Therefore, the VURx reliably predicts primary VUR improvement/resolution in children . The distal UDR is calculated as the widest diameter of the distal ureter in the false pelvis divided by the distance between L1 and L3 …”
Section: Are There Any Alternatives To Vcug?mentioning
confidence: 99%
“…Therefore, the VURx reliably predicts primary VUR improvement/resolution in children. [163][164][165] The distal UDR is calculated as the widest diameter of the distal ureter in the false pelvis divided by the distance between L1 and L3. 166 UDR measurement on the VCUG is objective, whereas the International Reflux Grading System is subjective.…”
Section: Prediction Of Vur Resolutionmentioning
confidence: 99%
“…Longitudinal studies have shown that ~50–65 % of cases of non-syndromic primary VUR undergo spontaneous resolution with age [2629]. Not much is known about the mechanism leading to this resolution, however the elongation of the intravesical ureter (0.5 cm at birth vs. 1.5–2.5 cm in adulthood) due to somatic growth has been offered as an explanation for the improved function of the UVJ [3032].…”
Section: Natural History Of Vurmentioning
confidence: 99%
“…10,38 The VUR index is a simple tool to predict the chance of spontaneous resolution in children under two years of age and assigns a score depending on the gender, bladder volume at onset of VUR, ureteral anatomy, and initial VUR grade. 39 In addition, other concomitant diagnoses may need to be considered and ruled out (e.g., posterior urethral valves, neurogenic bladder, etc. ).…”
Section: What Is the Probability Of Vur?mentioning
confidence: 99%